ANALYSIS OF BANK HEALTH LEVEL USING CAMEL AT BPRS MUAMALAT HARKAT BENGKULU TAHUN 2020-2023 - Dharma setiawan; Amir Mukadar; Marini; Dewi Sriwijayanti (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to evaluate the financial health of BPRS Muamalat Harkat Bengkulu from 2020 to 2023 using the CAMEL method, which encompasses five main components: Capital, Assets, Management, Earnings, and Liquidity. This study is crucial for determining the extent to which the bank's financial and operational performance meets the healthy criteria, while also providing objective information for management and stakeholders. The study population comprised all financial reports of BPRS Muamalat Harkat Bengkulu, with annual reports for the period studied as a sample. The data collection technique used was the documentation method, compiling secondary data in the form of balance sheets, income statements, and relevant financial ratios. Data analysis was conducted using descriptive quantitative analysis, calculating financial ratios based on CAMEL components, assigning scores according to the OJK assessment guidelines, and multiplying the results by the weights of each indicator to obtain a final score for the bank's health level. The research findings indicate that, overall, BPRS Muamalat Harkat Bengkulu was in the